Muxeninity and the Institutionalization of a Third Gender Identity in Alejandra Islas's Muxes: auténticas, intrépidas, buscadoras de peligro. - Subero, Gustavo (Hispanic Research Journal, 2013)
This article focuses on Alejandra Islas's documentary Muxes: auténticas, intrépidas, buscadoras de peligro (Mexico, 2005) and the way it demonstrates that transgenderism has become an institutionalized gender practice within Zapotec culture. It argues for an understanding of female relations and how they are experienced in the Isthmus in order to include muxes (a term that works as an umbrella for gay and transgender individuals) as part of the socio-sexual dynamics of the region. The article proposes a classification of the different types of Muxeninity (regarded as a separate gender category to the traditional male/female) that are encountered in this part of the country based on the different types of muxes that Islas shows in her documentary. It also argues that Muxeninity, as an identity, is not fixed or static but is an ever-evolving entity that is (re)constructed by not only an amalgamation of both ethnic identity (Zapotec) and transgender identity, but also of gay/queer as identity (as experienced in Anglo-European communities). Finally, it argues that the Vela de las muxes is a celebration that permits the conflagration of a diversity of expressions of Muxeninity, whilst demonstrating that this gender identity is multiple and fluid.